Potret Kehidupan Sosial Masyarakat pada Kumpulan Sajak Cinta dan Kisah-Kisah Yang Sulit Selesai Karya Gita Romadhona (Kajian Semiotika Michael Riffaterre) - Anwar, Rivaldi; Aryani, Aryani (CV. Eduartpia Publisher, 2023)
The main problem in the research in this study is about how the process of interpreting Heuristics and Hermeneutics and Social Criticism in the book collection of poems Love and Stories that are Difficult to Finish by Gita Romadhona. This study aims to determine the content of heuristic and hermeneutic meanings in the collection of poems Love and Stories that are Hard to Finish by Gita Romadhona. This type of research is a qualitative descriptive research. Using Michael Riffaterre's Semiotic study which covers the heuristic reading process and the hermeneutic reading process. The data in this study are in the form of data obtained from the results of the Heruristic and Hermeneutic discussion of the five poems contained in the collection of poems Love and Difficult Stories by Gita Romadhona, namely,